Analisis Pengaruh Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Tambang yang Terdaftar di Bursa Efek Indonesia Tahun 2013) - Arif Putranto, Fandiansyah, Dr. Anton Agus Setyawan, SE., M.Si (2016)
This research aims to analyze social responsibility disclosure of mining company listed on the Indonesia Stock Exchange and to provide empirical evidence that the corporate value has an influence on corporate social responsibility (CSR). The population of research was a mining company that has go public and listed on the Indonesia stock exchange in 2013 that a total of 27 companies. Methods of data analysis using classical assumption test, the test of normality, heteroscedasticity. Hypothesis testing includes simple linear regression test, t test and the coefficient of determination. The results of the research show the value of regression coefficient variable CSR is positive 0.727. It means that larger allocation and scope of company CSR will increase the corporate value. Thereby improving the CSR is not something that only useless, but very useful for company. More higher corporate social responsibility, will also increase the corporate value. CSR variable significant positive take effect on corporate value variable. R Square value in this research is 0.529 it means that 52.9% corporate value variable can be explained by the independent CSR variable. While the rest of 47.1% is explained by other factors that are not included in this research.